Culture of equine bone marrow mononuclear fraction and adipose tissue-derived stromal vascular fraction cells in different media - Ribeiro, Gesiane; Massoco, Cristina O.; Lacerda Neto, José Corrêa De [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2013)
The objective of this study was to evaluate the culture of equine bone marrow mononuclear fraction and adipose tissue - derived stromal vascular fraction cells in two different cell culture media. Five adult horses were submitted to bone marrow aspiration from the sternum, and then from the adipose tissue of the gluteal region near the base of the tail. Mononuclear fraction and stromal vascular fraction were isolated from the samples and cultivated in DMEM medium supplemented with 10% fetal bovine serum or in AIM-V medium. The cultures were observed once a week with an inverted microscope, to perform a qualitative analysis of the morphology of the cells as well as the general appearance of the cell culture. Colony-forming units (CFU) were counted on days 5, 15 and 25 of cell culture. During the first week of culture, differences were observed between the samples from the same source maintained in different culture media. The number of colonies was significantly higher in samples of bone marrow in relation to samples of adipose tissue.

O objetivo deste estudo foi avaliar o cultivo de células da fração mononuclear da medula óssea e da fração vascular estromal do tecido adiposo de equinos em dois diferentes meios. Cinco cavalos foram submetidos à aspiração da medula óssea do esterno e à coleta de tecido adiposo da região glútea, próxima à inserção da cauda. A fração mononuclear e a fração vascular estromal foram obtidas das amostras e cultivadas em meio DMEM suplementado com soro fetal bovino a 10% ou em meio AIM-V. As culturas foram observadas uma vez por semana com um microscópio de luz invertida, com o intuito de se realizar uma análise qualitativa das características morfológicas das células, bem como do aspecto geral do cultivo celular. As unidades formadoras de colônia (CFU) foram contadas nos dias 5, 15 e 25 do cultivo celular. Durante a primeira semana, foram observadas diferenças entre amostras obtidas de mesma origem mantidas em diferentes meios. O número de colônias foi significativamente maior nas amostras de medula óssea em relação às amostras de tecido adiposo.
Cultivo de células da fração mononuclear da medulla óssea e da fração vascular stromal do tecido adipose de equinos em diferentes meios
Keywords: Horse; bone marrow; adipose tissue; Culture medium; Cavalos; Medula óssea; Tecido adiposo; meios de cultura